Multi-alignment under "Uneven Multipolarity": India’s Relations with Russia in an Evolving World Order - Nivedita Kapoor (Vestnik MGIMO-Universiteta)
The article explores the ongoing evolution of India's relationship with Russia, using the concept of "uneven multipolarity" and its specific distribution of capabilities. It argues that India's perception of the balance of threats has shifted with respect to China, particularly in the Asia-Pacific and Indian Ocean regions, which are crucial to India's national security and future power projection ambitions. In the current context of uneven multipolarity, the capabilities of the US and China exceed those of weaker major powers, such as India, Russia, and Japan, without tipping the system into explicit bipolarity. This specific nature of current polarity and India's "China challenge" have led to shifting alignments in its foreign policy.When combined with changes in Russia's external relations, particularly the breakdown of its relations with the West and growing closeness with China, these factors have created particular constraints on New Delhi's partnership with Moscow. Multi-alignment for India represents a choice other than the formation of alliances as a balancing response, but it does introduce a hierarchy in its foreign relations. Under prevailing conditions, it emphasizes the importance of the relationship with the US while diminishing the significance of the relationship with Russia, even as the value of the bilateral partnership is retained in specific ways. These observations are instrumental in the assessment of the present and future trajectory of Indo-Russian ties presented in the article.